PENGARUH PUPUK N DAN JARAK TANAM TERHADAP PETUMBUHAN DAN HASIL KEDELAI PADA TANAH ALLUVIAL - Triponia, Weni; Abdurrahman, Tatang; Sulistyowati, Henny (Jurnal Sains Mahasiswa Pertanian, 2019)
The research aims to determine the interaction of fertilizer N and spacing, obtain the dosage of N fertilizer, and the best spacing of the growth and yield of soybean in aluvial soil. The research was carried out in the garden of the Faculty of Agriculture, Tanjungpura University, starting on May until JulyÂ 2018. The experiencest was Â in factorial based on completely randomized design (CRD) consisting of two factors namely fertilizer N and spacing. The N fertilizer dosage factor consisted of 3 levels of treatment namely 50 kg / ha, 100 kg / ha, and 150 kg / ha, and the spacing factor consisted of 3 treatment levels, namely 20 cm x 20 cm, 25 cm x 25 cm, and 30 cm x 30 cm, each treatment was repeated 3 times. The results showed no interaction between fertilizer N and spacing. N fertilizers with various doses give the same results for variable plant height, branch number, plant dry weight, root volume, seed weight per plant, and seed weight per plot. The spacing can increase the number of branches, root volume, seed weight per plant, and efficient spacing of 25 cm x 25 cm.Â Key Words : aluvial soil, N fertilizer, spacing, soybean